Evaluating migraine with typical aura with neuroimaging - Nazia Karsan; Nazia Karsan; Elisa Silva; Peter J. Goadsby; Peter J. Goadsby; Peter J. Goadsby (Frontiers in Human Neuroscience, 2023)
ObjectiveTo provide an up-to-date narrative literature review of imaging in migraine with typical aura, as a means to understand better migraine subtypes and aura biology.BackgroundCharacterizing subtypes of migraine with typical aura and appreciating possible biological differences between migraine with and without aura, are important to understanding the neurobiology of aura and trying to advance personalized therapeutics in this area through imaging biomarkers. One means of doing this over recent years has been the use of increasingly advanced neuroimaging techniques.MethodsWe conducted a literature review of neuroimaging studies in migraine with aura, using a PubMed search for terms ‘imaging migraine’, ‘aura imaging’, ‘migraine with aura imaging’, ‘migraine functional imaging’ and ‘migraine structural imaging’. We collated the findings of the main studies, excluding small case reports and series with n < 6, and have summarized these and their implications for better understanding of aura mechanisms.ResultsAura is likely mediated by widespread brain dysfunction in areas involving, but not limited to, visual cortex, somatosensory and insular cortex, and thalamus. Higher brain excitability in response to sensory stimulation and altered resting-state functional connectivity in migraine sufferers with aura could have a genetic component. Pure visual aura compared to visual aura with other sensory or speech symptoms as well, may involve different functional reorganization of brain networks and additional mitochondrial dysfunction mediating more aura symptoms.ConclusionThere is a suggestion of at least some distinct neurobiological differences between migraine with and without aura, despite the shared phenotypic similarity in headache and other migraine-associated symptoms. It is clear from the vast majority of aura phenotypes being visual that there is a particular predisposition of the occipital cortex to aura mechanisms. Why this is the case, along with the relationships between cortical spreading depression and headache, and the reasons why aura does not consistently present in affected individuals, are all important research questions for the future.